Heterophase synthesis of cobalt ferrite - E. E. Nikishina (Тонкие химические технологии)
Objectives. The study aimed to develop new methods for the synthesis of cobalt ferrite (CoFe2O4), which is a precursor for the synthesis of CoFe2O4-based functional materials, as well as to study the physicochemical properties of the obtained phases.Methods. Two methods were used for the synthesis of CoFe2O4: (1) heterophase interaction of hydrated iron oxide with cobalt(II, III) oxide and (2) heterophase interaction of hydrated iron oxide with an aqueous solution of cobalt(II) sulfate (CCo = 0.147 mol/L, solid/liquid = 1:43). In both cases, the precursor was hydrated iron oxide (Fe2O3, 84.4 wt %), which was obtained by the heterophase interaction of iron(III) chloride with a concentrated ammonia solution (6.0–9.5 mol/L). The resulting intermediate products were subjected to thermal treatment at 750 °C (synthesis 1) and at 900 °C (synthesis 2) for 10–30 h in increments of 10 h. The synthesized phases and products of their thermolysis were studied by differential thermal analysis and differential thermogravimetry (DTA–DTG), X-ray diffraction analysis (XRDA), and granulometry.Results. The hydrated iron oxide sample remained amorphous even up to the crystallization temperature of 445 °C, which corresponds to the exothermic effect on the DTA curve. Further heating led to the α-modification of iron(III) oxide of the hexagonal system (a = b = 5.037 ± 0.002 Å; c = 13.74 ± 0.01 Å), which has an average particle size of 1.1 μm. XRDA results showed that a synthesis temperature of 750 °C (synthesis 1) and a heat treatment duration of 30 h were sufficient for the formation of a single-phase cobalt ferrite (a = 8.388 ± 0.002 Å) with an average particle diameter of 1.9 μm. For synthesis 2, a higher temperature of 900 °C was used because sample weight loss (about 12.5%) was observed in the temperature range of 720–810 °C based on the DTA results, which was due to the removal of SO2 and SO3. Moreover, when synthesis temperature and duration were at 900 °C and 30 h, respectively, CoFe2O4 with a = 8.389 ± 0.002 Å was formed. The results of the granulometric analysis showed that particles of different diameters were formed. The smallest particle size (1.5 μm) of cobalt ferrite was obtained by the heterophase interaction of hydrated iron(III) oxide (Fe2O3, 84.4 wt %) with an aqueous solution of cobalt sulfate with CCo = 0.147 mol/L. Conclusions. Depending on the method used for the synthesis of cobalt ferrite, particles of different diameters are formed. The smallest particle size of cobalt ferrite was obtained from the heterophase interaction of hydrated iron(III) oxide with an aqueous solution of cobalt(II) sulfate.